2018
DOI: 10.1177/1556264618783834
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Views About a Paternal Consent Requirement for Biomedical Research in Pregnancy

Abstract: Clinical research to inform the evidence base to guide nonobstetrical care during pregnancy is critically important for the well-being of women and their future offspring. Conversations about regulations for such research, including whether paternal consent should ever be required, should be informed by the perspectives of those most affected, namely, pregnant women. We conducted in-depth interviews with 140 pregnant women living with or at risk of HIV-70 in Malawi, 70 in the United States-exploring their view… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 18 publications
2
49
0
Order By: Relevance
“…The data for this analysis were collected as part of a larger project, PHASES, which aims to develop guidance for ethically acceptable research on HIV treatment and prevention during pregnancy. We conducted qualitative, in-depth interviews using a semi-structured guide, as described previously [20]. The data for this analysis, collected between August 2016 and April 2017, pertain to women’s opinions about common contraception requirements for women participating in clinical trials.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data for this analysis were collected as part of a larger project, PHASES, which aims to develop guidance for ethically acceptable research on HIV treatment and prevention during pregnancy. We conducted qualitative, in-depth interviews using a semi-structured guide, as described previously [20]. The data for this analysis, collected between August 2016 and April 2017, pertain to women’s opinions about common contraception requirements for women participating in clinical trials.…”
Section: Methodsmentioning
confidence: 99%
“…The analytic approach was informed by thematic analysis [28], and described in detail elsewhere [20]. Interviews were recorded, transcribed verbatim, and translated as necessary.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Work in the social sciences has demonstrated the ways in which human agency, and in this case women's agency, is in practice bounded by the views and influences of important others (Burkitt, 2016;Duncan, 2015). For example, a recent study reported that a majority of women supported the requirement for paternal consent for pregnant women's participation in clinical trials that offer the prospect of direct benefit solely to the unborn baby (Sullivan et al, 2018). What remains challenging, even with these more nuanced models of socially situated decision making, is how to distinguish between mutually valued social support for women's decisions and more problematic, paternalistic norms that view women as unable to make decisions over their health and body once they become pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…The published studies identified differed in many ways from this paper, which focuses on the conditions under which the informed consent of the biological, legal and social father should be required in prenatal research on unproven but promising stem cell therapies. A recent, but rare, exception is a general study of women's views on a paternal consent requirement for biomedical research in pregnancy(Sullivan et al 2018).…”
mentioning
confidence: 99%